Introduction of an N-Glycosylation Site Increases Secretion of Heterologous Proteins in Yeasts - Sagt, C. M. J. (American Society for Microbiology, 2000)
Saccharomyces cerevisiae is often used to produce heterologous proteins that are preferentially secreted to increase economic feasibility. We used N-glycosylation as a tool to enhance protein secretion. Secretion of cutinase, a lipase, and llama V(HH) antibody fragments by S. cerevisiae or Pichia pastoris improved following the introduction of an N-glycosylation site. When we introduced an N-glycosylation consensus sequence in the N-terminal region of a hydrophobic cutinase, secretion increased fivefold. If an N-glycosylation site was introduced in the C-terminal region, however, secretion increased only 1.8-fold. These results indicate that the use of N glycosylation can significantly enhance heterologous protein secretion.